Effect of Debt Financing on Firm Performance: A Study on Energy Sector of Saudi Arabia - Ali, Anis; Shaik, Abdul Rahman (International Journal of Energy Economics and Policy, 2022)
The current research seeks to investigate the influence of debt financing (as assessed by the debt-equity ratio) on financial performance as evaluated by ROA and ROE. The information was taken from yearly reports issued by Saudi Arabian oil companies between 2012 and 2019. The current ratio (CR) was also incorporated as an interaction variable in the research. The findings indicate that debt financing has a detrimental influence on business financial performance. Furthermore, even after accounting for the interaction variable, the effect remains negative. Moreover, the business size has a negative link with the ROA and ROE.